2018
DOI: 10.1038/s41593-018-0126-0
|View full text |Cite
|
Sign up to set email alerts
|

A hypothalamic circuit for the circadian control of aggression

Abstract: “Sundowning” in dementia and Alzheimer’s disease is characterized by early evening agitation and aggression. While such periodicity suggests a circadian origin, whether the circadian clock directly regulates aggressive behavior is unknown. We demonstrate that a daily rhythm in aggression propensity in male mice is gated by GABAergic subparaventricular zone (SPZGABA) neurons, the major postsynaptic targets of the central circadian clock, the suprachiasmatic nucleus (SCN). Optogenetic mapping revealed that SPZGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
114
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 58 publications
(86 reference statements)
7
114
0
Order By: Relevance
“…Fig. S2A-C), a structure that has recently been shown to mediate circadian control of aggression via indirect projections to VMHvl Esr1 neurons(52). Finally, although VMHvl Esr1 neurons exhibit very weak direct projections to mPFC,(Fig.…”
mentioning
confidence: 88%
“…Fig. S2A-C), a structure that has recently been shown to mediate circadian control of aggression via indirect projections to VMHvl Esr1 neurons(52). Finally, although VMHvl Esr1 neurons exhibit very weak direct projections to mPFC,(Fig.…”
mentioning
confidence: 88%
“…Aggression is a complex social behavior and different kinds of aggressive behavior may be evoked by different contextual cues under defined internal states and environmental conditions. Several brain regions including olfactory, amygdalar, and hypothalamic loci have been found to be essential for inter-male aggression in rodents (Chamero et al, 2007; Hong et al, 2014; Leroy et al, 2018; Leypold et al, 2002; Lin et al, 2011; Mandiyan et al, 2005; Stagkourakis et al, 2018; Stowers et al, 2002; Todd et al, 2018). A few identified neural circuits for controlling distinct types of aggression, including predatory aggression (Han et al, 2017; Li et al, 2018; Park et al, 2018; Shang et al, 2019; Zhao et al, 2019), female or maternal aggression (Hashikawa et al, 2017; Unger et al, 2015), and pup-directed aggression (Chen et al, 2019; Isogai et al, 2018; Renier et al, 2016; Trouillet et al, 2019; Tsuneoka et al, 2015) have also been reported recently in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Animals exhibit a range of aggressive behaviors (Blanchard et al, 2003; Moyer, 1968) essential for survival, reproduction, and social hierarchy establishment (Nelson and Trainor, 2007), while pathological aggression and the inability to control aggressive states cause serious social problems (Coccaro, 2012; Davidson, 2000; Siegel and Victoroff, 2009). Distinct regions in the mouse brain have been shown to be essential for male (Chamero et al, 2007; Hong et al, 2014; Lee et al, 2014; Leroy et al, 2018; Lin et al, 2011; Stagkourakis et al, 2018; Stowers et al, 2002; Todd et al, 2018; Unger et al, 2015; Yang et al, 2013; Yang et al, 2017; Zelikowsky et al, 2018), female (Hashikawa et al, 2017; Unger et al, 2015), predatory (Han et al, 2017; Li et al, 2018; Park et al, 2018; Shang et al, 2019; Zhao et al, 2019), and infant-directed (Autry et al, 2019; Chen et al, 2019; Isogai et al, 2018; Trouillet et al, 2019) aggressive behaviors. Furthermore, studies from some brain regions that have been examined for more than one type of aggressive behaviors suggest that different behaviors are regulated by distinct, dedicated neural circuits under specific internal and external conditions (Chen and Hong, 2018; Chen et al, 2019; Han et al, 2017; Hashikawa et al, 2017; Isogai et al, 2018; Yang et al, 2017; Zelikowsky et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that these experiments were performed during the light cycle, a period of lower activity levels for nocturnal rodents such as mice. While the mechanism is not fully elucidated, aggressive behaviors do show variability across the light-dark cycle 58 . Circadian rhythms may also crucially affect the LHb in particular, which may subsequently exert varying effects throughout the light-dark cycle on downstream targets regulating a variety of motivated behaviors 59 .…”
Section: Discussionmentioning
confidence: 99%